Angel Unaware, Cognitive Disability, and the Politics of Positive Thinking - Walker-Cornetta, Andrew (Religion and American culture, 2023)
This article focuses on what may very well be the most popular text about cognitive disability in US American history. Released in 1953, Angel Unaware told the story of Hollywood stars Dale Evans’ and Roy Rogers’s experiences raising a young daughter who had been diagnosed at birth with what her mother referred to as an "appalling handicap" (what would later be labeled Down Syndrome). Situating this work and its reception within existing scholarship on postwar religion in the United States, this essay offers a novel interpretation of positive-thinking Christianity by showing how its grammars inspired and underwrote a nascent politics of disability for parents of "exceptional" children and their allies. In doing so, it not only underscores how religion has shaped notions of human difference in US American culture but also identifies disability as a crucial and heretofore neglected site of American religion making.